Determinan Kepatuhan Pajak - Janti Saragih (Jurnal Keuangan dan Perbankan, 2014)
This study aims to obtain new empirical evidence regarding: (1) the factors that affect tax compliance, and (2) differences in tax compliance based on: the type of taxpayer, classification and sources of income. This study uses cross section data period 2001-2011 obtained through field research in one of the Regional Office of Directorate General of Taxation and is estimated using Ordinary Least Square method approach Newey West. The results showed that the amount of income, income taxes, penalties, the probability of an audit, the audit frequency and experience to fill the SPT either individually or jointly significant positive effect on tax compliance. Through testing different between groups, corporate taxpayers are relatively more adherent than an individual, a high-income taxpayer, more obedient than the relatively low-income taxpayers, taxpayers operating in the service sector, relatively less adherent than taxpayers operating in the trade sector, while taxpayers operating in the industrial sector, relatively more adherent than taxpayers operating in the trade sector